Preoperative Attention/Memory Problem Affects the Quality of Life of Parkinson’s Disease Patients after Deep Brain Stimulation: A Cohort Study - Ying Gao; Jue Wang; Linbin Wang; Dianyou Li; Bomin Sun; Xian Qiu (Parkinson's Disease)
Objectives. The aim of this study was to investigate the impact of nonmotor symptoms (NMS) on the quality of life (QoL) outcome after subthalamic nucleus deep brain stimulation (STN-DBS) at the 1-year follow-up. Methods. Ninety-three patients diagnosed with Parkinson’s disease (PD), who underwent subthalamic nucleus deep brain stimulation (STN-DBS) between April 2020 and August 2021, were included in this study. Demographic information was gathered through a self-designed questionnaire. The severity of both motor and non-motor symptoms, along with the quality of life (QoL), was assessed using the Unified Parkinson’s Disease Rating Scale-III (UPDRS-III), Nonmotor Symptoms Scale (NMSS), and 8-item Parkinson’s Disease Questionnaire (PDQ-8), respectively. Results. Significant differences were observed in the UPDRS-III score, NMSS summary index (SI), and subscores of six domains (sleep/fatigue, mood/cognition, perceptual problems/hallucinations, attention/memory, urinary, and sexual function) between the baseline and the 6- and 12-month follow-ups. The correlation analysis revealed positive correlations between the preoperative NMSS SI and subscores of seven domains (cardiovascular, sleep/fatigue, mood/cognition, perceptual problems/hallucinations, attention/memory, gastrointestinal, and urinary) and ΔPDQ-8. Moreover, the preoperative PDQ-8 SI (β = 0.869, P<0.001) and the preoperative attention/memory subscore (β = −0.154, P=0.026) were predictive of the postsurgery improvement in quality of life (QoL). Conclusion. Deep brain stimulation (DBS) led to an improvement in the patients’ nonmotor symptoms (NMS) at the 1-year follow-up, along with a correlation observed between NMS and the patients’ quality of life (QoL). Notably, the severity of preoperative attention/memory problems emerged as the most significant predictor of NMS influencing the QoL outcome after STN-DBS at the 1-year follow-up.